Pacific Island Women’s Experiences of the ‘Brown Glass Ceiling’ in Senior Management in Aotearoa New Zealand - Mesui, Mary Lopakitea (Auckland University of Technology, 2019)
Research has illustrated how the glass ceiling hinders women from entering senior management roles. In addition, research has shown that ethnic women experience additional barriers because of their ethnicity and culture. The purpose of this dissertation is to provide visibility to the experiences of Pacific women in senior management in Aotearoa New Zealand and identify underlying factors that are contributing to their underrepresentation in senior management positions. This research uses a qualitative methodology with data collected through semi structured interviews. The findings illustrate the challenges, support systems, and strategies utilised to overcome workplace challenges for Pacific women. Specifically, racism, institutional racism and cultural values have impacted Pacific women through racial stereotypes, tokenism and not fitting into Westerns perceptions of the ideal manager. What has alleviated the challenges Pacific women have faced in advancing into senior management is support such as spirituality, family, organisational support and mentoring. Pacific women in this study demonstrated coping strategies such as gaining higher qualifications and assimilating into Western organisations culture, often at the cost of minimising their cultural identity. Consequently, this research demonstrates how the ‘brown glass ceiling’ impacts Pacific women’s career journeys into senior management, with the aim to provide solutions that will help improve the number of Pacific women entering senior management positions.
Keywords: Brown Glass Ceiling; Pacific Women; Senior management; Racism